The interaction of relative age with maturation and body size in female handball talent selection - Tróznai, Z.; Utczás, K.; Pápai, J.; Pálinkás, G.; Szabó, T.; Petridis, L. (PLOS ONE, 2024)
The relative age effects (RAEs) and biological maturation are two distinct factors that have been identified to affect talent identification and selection. Previous research has suggested that talent selection should include sport-specific technical tasks instead of body size and/or physical test measurements, assuming that the technical tasks are less influenced by variations in maturation. Our purpose was to examine the prevalence of RAEs and to assess biological maturity, body size, and body composition within a single talent selection program for female handball players. Team coaches` recommendations, handball-specific drills, and in-game performance were the selection criteria. Birth distribution of all U14 female handball players were analysed (N = 3198) grouped in two-year age cohort. Measurements of body size, body composition (InBody 720), and bone age were performed in all players who were selected to participate in the selection program (n = 264) (mean±sd age: 13.1±0.6 years) and in a sample of not-selected players (n = 266) (mean±sd age: 13.2±0.6 years). Players were grouped in quarter-year intervals based on their date of birth. Chi-square was used to examine quartile distributions, differences between quartiles were tested with one-way analysis of variance, whereas differences between the selected and not-selected groups were examined with independent sample t-test (Cohen d effect size). Binary logistic regression was used to determine the effects of the predictors on the selection. In terms of all registered players, there was no difference in birth distribution. RAEs appeared at the first selection stage and were evident at all following stages. Quartiles differed only between the first and the last quartiles in body size and muscle mass. Only bone age differed between consecutive quartile or semi-year groups. Body size, body composition, and maturity had a significant, but of moderate power, effect on the selection. Larger body height increased the likelihood of selection by about 12%, larger muscle mass by 12% to 25%, larger bone age by 350-400%, while larger percent body fat decreased selection chances by 7%. The sport-specific criteria could not eliminate the prevalence of the RAEs. Relative age was connected to bone age, but not convincingly to body size and muscle mass. Although bone age had the largest effect on the selection, this was not associated with larger body size or muscle mass. Early maturation increased selection chances mainly during the coaches` subjective evaluation, but not convincingly when sport-specific tasks were applied. Given that differences were mostly evident between players of more than 1.5-year variation in their chronological age, one-year age cohorts within talent selection or the rotation of the cut-off dates of the bi-annual age grouping could be a promising strategy while also including maturation status and relative age in performance evaluations.